2021
DOI: 10.3390/antibiotics10080985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Carbohydrate Sources Nectar, Sucrose and Invert Sugar on Antibacterial Activity of Honey and Bee-Processed Syrups

Abstract: Honey is a functional food with health-promoting properties. Some types of honey are used in wound care for the treatment of acute and chronic infected wounds. Increased interest in using honey as a functional food and as a base for wound care products causes limited availability of raw honey. Numerous studies suggest that the protein content of honey is mainly comprised of bee-derived proteins and peptides, with a pronounced antibacterial effect. Therefore, the aim of our study was to characterize for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…As a result, the antibacterial action against the studied bacteria was lowered, as was the efficacy of the exhibition. A study by Bugarova et al [ 43 ] showed that raw honey and adulterated honey give different amounts of sugar level thus reflecting the antibacterial activity of honey. Adulterated honey will give lower antimicrobial activity compared to raw honey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the antibacterial action against the studied bacteria was lowered, as was the efficacy of the exhibition. A study by Bugarova et al [ 43 ] showed that raw honey and adulterated honey give different amounts of sugar level thus reflecting the antibacterial activity of honey. Adulterated honey will give lower antimicrobial activity compared to raw honey.…”
Section: Resultsmentioning
confidence: 99%
“…Adulterated honey will give lower antimicrobial activity compared to raw honey. This sugar would be completely absent or present in minute amounts in honey that has been processed [ 43 ]. Observations made in accordance with nearly every study comparing the antibacterial capabilities of authentic and contaminated honey revealed that the efficacy of the prevention of bacterial species growth decreases as the amount of adulterated honey is increased.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, no correlation was found between H 2 O 2 and GOx and between H 2 O 2 and CAT (p > 0.05) (Table 2). A lack of correlation between GOx and H 2 O 2 was already reported, concluding that GOX activity is not a reliable parameter for the prediction of H 2 O 2 and the antimicrobial activity of honey [13,15,23,36]. In our study, there were four behavioral tendencies of the analyzed honeys regarding the CAT and GOx activities and H2O2 concentration, which can be divided into four different cases: In our study, there were four behavioral tendencies of the analyzed honeys regarding the CAT and GOx activities and H 2 O 2 concentration, which can be divided into four different cases:…”
Section: Hydrogen Peroxide Concentrationmentioning
confidence: 99%
“…When honey is diluted, GOx is activated [11]. Thus, we consider that it is of utmost importance to determine the real activity of GOx instead of the GOx content that was already measured by other researchers [13,15,23]. Therefore, the purpose of this research was to determine the possible relationships among CAT and GOx activities, the concentration of H 2 O 2 , and the antimicrobial activity of honeys against Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Honey is rich in nutrients and active ingredients (Wang et al ., 2021), such as sugars, water and minor constituents (Sogut & Seydim, 2020). Honey contains a variety of sugars, mainly fructose and glucose (Bugarova et al ., 2021). In addition, it also contains solid particulate matter (plant pollen) collected from the plant (Layek et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%